Profil Minat Karir Siswa serta Implikasi bagi Bimbingan dan Konseling - Indri Mulyadini; Raudah Zaimah Dalimunthe; Meilla Dwi Nurmala (Journal of Education and Counseling (JECO), 2022)
The purpose of this study was to describe the career interests of students in Class XI MAN throughout Pandeglang Regency for the 2020/2021 academic year. This study uses a descriptive research method with a quantitative approach, the object of research is 268 students of class XI. Aspects of career interest consist of six personality types, namely realistic, investigative, artistic, social, enterprising and conventional. The data collection technique is a questionnaire in the form of a questionnaire. Based on the results of the instrument validity test that has been carried out, it produces as many as 60 valid items. As for the results of the reliability test, the number is 0.818 with a very strong/high classification. The results showed that the career interests of class XI MAN students throughout Pandeglang Regency were in the medium category with a percentage of 55% as many as 148 students, in the low category with a percentage of 23% as many as 62 students and in the high category with a percentage of 22% with a percentage of 58 students.